2022
DOI: 10.1007/s00590-022-03364-2
|View full text |Cite
|
Sign up to set email alerts
|

Lower limb post-traumatic osteomyelitis: a systematic review of clinical outcomes

Abstract: Purpose The aim of this study was to examine the patient-reported outcomes of patients presenting with post-traumatic osteomyelitis (PTOM) of the lower limb over the past 15 years. This period was chosen to reflect modern treatment principles and increased centralisation of care. Methods An electronic literature search of the relevant databases (PubMed, Ovid Medline, Embase, and the Cochrane library) was conducted to identify studies published between Janu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 47 publications
(112 reference statements)
1
2
0
Order By: Relevance
“…In contrast, the total non-infection-related complication rate was 15.6% after the first stage and 17.8% after the second stage, in line with rates reported in the literature [2,13,27,50]. There were only two above-the-knee amputations, both related to re-infection, with an amputation rate of 4.4%, similar to the amputation rate reported in patients undergoing a two-stage procedure for the first episode of knee infection (4%) [52]; the amputation rate for chronic post-traumatic osteomyelitis, on the other hand, is reported to be up to 17% [53,54].…”
Section: Discussionsupporting
confidence: 83%
“…In contrast, the total non-infection-related complication rate was 15.6% after the first stage and 17.8% after the second stage, in line with rates reported in the literature [2,13,27,50]. There were only two above-the-knee amputations, both related to re-infection, with an amputation rate of 4.4%, similar to the amputation rate reported in patients undergoing a two-stage procedure for the first episode of knee infection (4%) [52]; the amputation rate for chronic post-traumatic osteomyelitis, on the other hand, is reported to be up to 17% [53,54].…”
Section: Discussionsupporting
confidence: 83%
“…When combined with antibiotics such as gentamicin, calcium sulphate provides a valuable tool in providing a high concentration of local antimicrobial that elutes over a period of 4 weeks ( 133 ). The use of local antibiotics has revolutionised the management of long bone fracture-related infection, reducing recurrence rates from 30 to 40%, to less than 10% ( 134 , 135 , 136 ). Calcium sulphate bone substitutes have also been demonstrated to be efficacious when managing small bone defects (<1 cm), with graft resorption and new bone incorporation occurring over a course of 6 months with good clinical results ( 137 ).…”
Section: Synthetic Bone Substitutesmentioning
confidence: 99%
“…In their recent systematic review on clinical outcomes of PTOM over the last 15 years Rodham et al [37 ▪▪ ] report an overall eradication rate of PTOM of 93.2% across 16 studies. Noteworthy, the primary remission rates within the studies included in the systematic review were reported ranged between 43% and 91%.…”
Section: Can We Predict Outcome After Treatment Of Long Bone Osteomye...mentioning
confidence: 99%